5 - Should There Be a General Subsidy for Higher Education in Developing Countries? David E. Bloom & Jaypee Sevilla - David E. Bloom; Jaypee Sevilla (Journal of Higher Education in Africa, 2003)
The view that developing countries ought to offer general subsidies for higher education has many supporters. We use traditional economic logic to specify the conditions under which such an investment policy would promote a so- cially efficient allocation of resources. We identify three necessary conditions. First, the net social benefit from the investment must be positive. Second, pri- vate actors must have insufficient ability or incentive to undertake the socially optimal level of investment. Finally, the investment must generate more net social benefits than competing uses of public funds. We reason that the first condition is likely to be satisfied, the second might not, and third is even more questionable. Without empirical evidence to the contrary, we therefore reason that there is no clear-cut efficiency reason for a general subsidy for higher education in developing countries.